The Effect of HDI and Macroeconomic Variables on Economic Growth in Indonesia 2015-2020 - Soleman, Riky; Ebiyeska, Hedi; Wibowo, Muhammad Ghafur; Nainggolan, Basaria (Jurnal Ilmu Ekonomi Terapan, 2022)
The Human Development Index (HDI) measures the achievement of human development based on several basic components of quality of life. HDI is built through a basic three-dimensional approach to measure the quality of life. These dimensions include life expectancy and health, knowledge, and a decent life. Stable inflation is a prerequisite for the realization of economic growth and social welfare. Different economic conditions and natural conditions make inflation between regions in Indonesia varied. This study aims to examine HDI, inflation, investment and labor on Indonesia's economic growth. The data source used in the form of panel data that obtained from the Badan Pusat Statistik (BPS) for the 2015-2020 period. Using panel regression data with the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approach processed with E-Views 10. The results of this study indicate that the estimated model chosen in this study is Fixed Effect Models (FEM). The partial test shows that the HDI, CPI, and INV variables have a significant positive effect on economic growth. In contrast, the probability value of labor (L) does not have a significant effect on economic growth. Meanwhile, in the simultaneous test, the F-statistic probability value is 0.000000 < 0.05, which means that the four independent variables simultaneously affect economic growth. Furthermore, the Adjusted R-Square value is 0.0994749, which means 99% of the HDI, CPI, INV, and L variables in this study can explain the variation of economic growth variables. While the remaining 1% is explained by other variables outside the model.